Bifrontal active and sham rTMS in treatment-resistant unipolar major depression. (17th November 2018) - Valkonen-Korhonen, Minna; Leinola, Hanna; Könönen, Mervi; Niskanen, Eini; Purhonen, Maija; Pakarinen, Maarit; Ruusunen, Anu; Lehto, Soili M.; Mervaala, Esa; Honkalampi, Kirsi; Koivumaa-Honkanen, Heli; Viinamäki, Heimo
Abstract: Background and aim: Prevention of the recurrence of major depression and its residual symptoms requires effective treatment. Our aim was to study the effects of bifrontal active rTMS controlled by sham rTMS in treatment-resistant unipolar major depressive disorder (MDD). Methods: Thirty-seven patients with treatment-resistant MDD were randomized into two groups. One group received a total of 30 sessions of active bifrontal rTMS (10 Hz rTMS on left dorsolateral prefrontal cortex (DLPFC) and 1 Hz rTMS on right DLPFC) and the other group received bilateral sham rTMS on five days a week for six weeks. Results: Depressive symptoms significantly improved in both the groups, but without a significant group difference. Furthermore, patients with psychotic depression improved similarly to those with moderate or severe depression. Conclusions: The results of present study indicate a large sham effect of stimulation treatment. The intensive structured treatment protocol may explain the positive outcome in both the groups. It is important to recognize, appreciate, and utilize placebo effects as a significant means of rehabilitation in psychiatric care.